Evaluation of revitalisation projects in Poland using the Maslin Multi-Dimensional Matrix. Heading towards green & social revitalisation - Starczewski, Tomasz; Krzysztof, Rogatka; Kowalski, Mateusz (Bulletin of Geography. Socio-economic Series, 2022)
One of the greatest challenges currently facing cities is the evaluation of the revitalisation process, i.e., verifying whether and to what extent it has been successful. This assessment is important as it will determine the extent to which the revitalisation needs of a place have been met. The aim of this article is to present the results of the evaluation of a post-revitalisation space made by its users and to determine the usefulness of the Maslin Multi-Dimensional Matrix (MMDM) method used. This is the first attempt, not previously reported in the literature, to use the MMDM for evaluating revitalisation. According to research, projects of an integration and environmental character and those improving security were the most appreciated and at the same time had the best revitalising effect on the Bydgoskie Przedmieście district in Toruń, Poland. The lowest ratings were given to infrastructural projects or those dedicated to narrow social groups (alternative arts). The MMDM method should be considered an appropriate tool for evaluating revitalisation.